A Critical Approach to A Concise Introduction to Mixed Methods Research with Rhetorical Analysis - Mahdi Shaghaghi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this article, I tried to investigate the rhetorical aspects of Creswell’s “A Concise Introduction to Mixed Methods Research” with a critique of the Persian translation of the book. After the introduction and problem statement and methodology, I tried to introduce all sections of the book, describe its formal aspects, and trace standpoint of the work among similar works and then mention the main weaknesses of the Persian translation, which include machinist translation, editorial errors, pronunciation problems, errors in finding fitted equivalent terms, disruption in harmonious use of phrases, misspellings and so on. Then by using Spurr’s (1993) model of rhetoric analysis, I tried to extract sample sentences from important sections of the book that explicitly have rhetorical acts and categorize them. This rhetorical aspect would be the point of departure for a methodological discussion about the pre-assumptions of this structure for research.